Anti-tumor necrosis factor alpha treatment does not influence serum levels of the markers associated with radiographic progression in ankylosing spondylitis - Ali Erhan Özdemirel; Serdar Can Güven; Alper Doğancı; Zühre Sarı Sürmeli; Ayla Özyuvalı; Mehmet Kurt; Diana Rüstemova; Selin Hassan; Ayşe Peyman Yalçın Sayın; Hüseyin Tutkak; et al. (Archives of Rheumatology, 2023)
Objectives: The study aimed to determine the levels of change of the markers related to radiographic progression, such as Dickkopf-1 (DKK-1), sclerostin (SOST), bone morphogenetic protein (BMP)-2 and -4, and interleukin (IL)-17 and -23, in ankylosing spondyloarthritis (AS) during anti-tumor necrosis factor alpha (TNF-α) treatment. Patients and methods: Fifty-three anti-TNF-α naïve AS patients (34 males, 19 females; median: 38 years; range, 20 to 52 years) refractory to conventional treatments meeting the modified New York criteria or Assessment of SpondyloArthritis International Society classification criteria were enrolled to this cross-sectional, controlled study between October 2015 and January 2017. Fifty healthy volunteers (35 males, 15 females; median: 36 years; range, 18 to 55 years) with similar age and sex characteristics were recruited. Serum DKK-1, BMP-2, BMP-4, SOST, IL-17, and IL-23 levels were measured in both groups. The serum levels of the markers were measured again after about two years (mean follow-up duration of 21.7±6.4 months) in AS patients who started anti-TNF-α treatment. Demographic, clinical characteristics, and laboratory parameters were recorded. The disease activity at the time of inclusion was assessed through the Bath Ankylosing Spondylitis Disease Activity Index. Results: Serum DKK-1, SOST, IL-17, and IL-23 levels in the AS group before anti-TNF-a treatment were significantly higher compared to the control group (p<0.01 for DKK-1, p<0.001 for others). There was no difference regarding serum BMP-4 levels, whereas BMP-2 levels were significantly higher in the control group (p<0.01). Forty (75.47%) AS patients had serum marker levels measured after anti-TNF-α treatment. No significant change was observed in the serum levels of these 40 patients measured 21.7±6.4 months after the initiation of anti-TNF-α treatment (p>0.05 for all). Conclusion: In AS patients, there was no change in DKK-1/SOST, BMP, and IL-17/23 cascade with anti-TNF-α treatment. This finding may suggest that these pathways act independently of each other, and their local effects are not influenced by systemic inflammation.